2012
DOI: 10.1111/j.1467-985x.2012.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Varieties of English

Abstract: Linguistic corpora are databases of text which are linguistically marked up or otherwise structured and designed to be representative of a specific language.The growing availability of such corpora has brought with it opportunities for statistical analysis. The paper develops and uses statistical approaches to address questions pertaining to an important linguistic phenomenon: the use of different syntactic alternatives. We present a model-selection-based approach for determining possible driving attributes af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…To give but one example here of how a very different area in multilingualism research can benefit from a statistically sophisticated, corpus-based approach, see Gries and Bernaisch’s (in press) study, which uses MuPDAR to compare six southeast English varieties with the historical input variety, British English. Their analysis ultimately confirms previous, less data-driven studies which found that Indian English forms the linguistic epicenter of English for Southeast Asia – at least with regard to the dative alternation that forms the basis of their comparison (see also Nam, Mukherjee, Schilk, & Mukherjee, 2013; Schilk, Mukherjee, Nam, & Mukherjee, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…To give but one example here of how a very different area in multilingualism research can benefit from a statistically sophisticated, corpus-based approach, see Gries and Bernaisch’s (in press) study, which uses MuPDAR to compare six southeast English varieties with the historical input variety, British English. Their analysis ultimately confirms previous, less data-driven studies which found that Indian English forms the linguistic epicenter of English for Southeast Asia – at least with regard to the dative alternation that forms the basis of their comparison (see also Nam, Mukherjee, Schilk, & Mukherjee, 2013; Schilk, Mukherjee, Nam, & Mukherjee, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…As hinted in our introduction, in order to explore cross-variety variation at the lexis-grammar interface, ESL scholars are increasingly starting to adopt regression statistical approaches that allow them (i) to include in their analyses wide ranges of linguistic factors and (ii) to analyze alternating syntactic pairs by cutting across the semantic and morphosyntactic levels. For instance, Nam et al (2013) use this approach to investigate three complementation patterns of give (ditransitive, prepositional dative and monotransitive) and they begin to unveil the governing principles behind ESL speakers' choices of one construction over another. However, despite their usefulness, multifactorial approaches in ESL have mainly been used to investigate the dative alternation and their application remains to be extended to other syntactic alternations.…”
Section: The Contribution Of Grammatical Factors To Alternating Verb mentioning
confidence: 99%
“…In learner corpus research, studies such as Gries & Wulff (2013), Gries & Adelman (2014), , Deshors (to appear a, to appear b) are all multifactorial studies of alternative (lexical or grammatical) choices and all compare (in similar ways) the choices EFL and ENL speakers make and why. Similarly in variety research, studies like Bresnan & Hay (2008), Bresnan & Ford (2010), Bernaisch et al (2014), Nam et al (2013), Schilk et al (2013), and Deshors (to appear c) all explore the dative alternation and have been moving the field along to its current relatively sophisticated state of the art. This desirable development notwithstanding, all of the above studies still exhibit one or more shortcomings of the kinds discussed in the previous section: most of these studies do not account for lexical/speaker-specific variation, do not take the hierarchical structure of the corpora into consideration, and -perhaps one of the most fundamental issues -do not make explicit comparisons of non-native and native speaker choices in precisely defined contexts.…”
Section: Corpus-based Work On Alternationsmentioning
confidence: 99%